Intrastate Hydro Politics: Issues of Hydro Resource Management in India - Nusrat Asif; Asia Mukhtar; Dr. Hafiz Abdur Rashid (Journal of Political Studies, 2021)
This article addresses the intrastate hydro issues and conflicts in India. With the advancement of industrial development, the issue of hydro resource sharing and acquisition has emerged as a major issue in the country. Presently Indian states are facing serious disputes over the hydro resource sharing formulas and construction of mega water reservoirs over the shared water resources. Water deprivation has even compelled some states to demand for themselves a separate state, causing alienation from the Indian federation. This article strives to look into the parameters adopted by the federal government of India for resolution of the issues. It also investigates how India has been unable to adopt and devise a permanent hydro management policy. The expert view opines that if the grim hydro management situation is not addressed properly it may lead to water scarcity and consequent deteriorated internal political scenario. This article suggests that this issue can be resolved through viable hydro management strategies that involve all stakeholders with a positive purpose to satisfy each one of them. Ultimately, it is suggested that unless India improves its water sharing mechanisms with the neighboring countries, the internal strategies to resolve the issue would go in vain.